A Firm Size as a Moderator in the Influence of Financial Ratio Analysis and Cash Holding on Income Smoothing - Pawolung, Putri Dayana; Hariyanti, Widi; Harjito, Yunus; Siddiq, Faiz Rahman (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
This research aims to determine the influence of profitability, financial leverage, and cash holding on income smoothing practice with firm size as a moderating variable in banking companies during the period 2018-2022. The data used in this research is secondary data. The population of this reseacrh comprises all banking companies losted on the Indonesia Stock Exchange (IDX) for the 2018-2022 period with a total of 46 companies. The sample used consists of 29 companies, selected using the “purposive sampling” method. The result of the study show that profitability and cash holdings have a negative effect on Income smoothing, while financial leverage has a positive effect. In addition, this reseacrh proves that firm size cannot moderate the effect of profitability on income smoothing. However, it also proves that firm size can moderate the effect of financial leverage on income smoothing. Keywords: cash holding; financial leverage; firm size, income smoothing; profitability